1950
DOI: 10.1103/physrev.80.106
|View full text |Cite
|
Sign up to set email alerts
|

Ionization by Recoil Particles from Alpha-Decay

Abstract: which can be derived from considerations of the momentum space degeneracy of the outgoing particles.In line with the suggestions of Weisskopf, Feshbach, and Peaslee, 7 Wigner 8 has shown that widths are also proportional to level spacing, D } whence (6) becomes TacEW.Relation (5) must then be considered valid only in cases of neutron capture. Since level spacings in neutron capture are about 10 ev, in general, (5) must be replaced by r/£*£~4XlO-B (ev)-*.Applying (8) to the case of alpha-decay, JS*~2.5X10 3 (ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1951
1951
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…It is not clear how much of such effect is included in the asymptotic form. Ling and Knipp (1950) presented a model for Pb ions in Ar similar to the power low approximation by Lindhard. They estimated that about 2/3 of the ionization is due to the secondary ions.…”
Section: Resultsmentioning
confidence: 99%
“…It is not clear how much of such effect is included in the asymptotic form. Ling and Knipp (1950) presented a model for Pb ions in Ar similar to the power low approximation by Lindhard. They estimated that about 2/3 of the ionization is due to the secondary ions.…”
Section: Resultsmentioning
confidence: 99%
“…The curve is intended for directional searches for WIMPs in the gas TPC. Ling and Knipp [30] presented an approximate equation for q nc for a heavy particle (24) where γ" = 2M 1 / (M 1 + M 2 ) and a , a" are constants. They found that the measurement by Madsen [27] is well represented by the following equation:…”
Section: Heavy Recoil Ions In α-Decaymentioning
confidence: 99%
“…LET el for Pb recoils is as large as S T /3 in argon as shown in Figure 2a. Following Ling and Knipp [30], we use the W α /W NR ratio, (22.0 ± 0.3)/(158.8 ± 8) = 0.139, for 103 keV Pb recoils in Xe measured by Cano [29], and a semi-empirical power-law approximation may be written as…”
Section: Heavy Recoil Ions In α-Decaymentioning
confidence: 99%
See 1 more Smart Citation
“…Ling and Knipp [7] have presented an approximate equation for a heavy particle (Z=82, A= 208) in Ar.…”
Section: Z Zmentioning
confidence: 99%